Perlindungan Hukum Terhadap Desain Tata Letak Sirkuit Terpadu Ditinjau dari Perspektif Pidana Dalam Hukum Positif - Nazhif Ali Murtadho (LPPM Universitas Bina Taruna Gorontalo, 2024)
The main issues in Intellectual Property Rights are regarding legal protection, because Intellectual Property Rights are experiencing rapid development. Because IPR is exclusively owned by the creator and the legal protection prevents violations of Intellectual Property Rights by other parties who are not authorized by criminal sanctions. Indonesia has ratified the TRIPs Agreement, through Law No. 7 of 1994 and the issuance of Law Number 32 of 2000 concerning Layout Design of Integrated Circuits that are able to protect as well as secure and enforce legal protection oh the rights of creators in this case are the exclusive. Rights of every person (designer). By using normative methods with data collection techniques through literature studies to examine primary legal materials including legislation, secondary legal materials include expert opinions. DTLST according to article 1 paragraph (2) is the creation of a three-dimensional layout design of various active components and partly or wholly related in an integrated unit, 3D circuit layout is to prepare an integrated circuit. And the term of DTLST protection is 10 years from the date of registration.